COOPERATIVE DEVELOPMENT STRATEGY IN EFFORTS TO INCREASE COMPETITIVENESS IN KARAWANG REGENCY (CASE STUDY ON GROUP OF NON-EMPLOYEE COOPERATIVES IN KARAWANG REGENCY) - Nurdinasari, Siti; Isyanto, Puji (Jurnal Manajemen dan Bisnis Kreatif, 2017)
Abstract The purpose of the research to find out how the implementation of non-employee cooperative management strategy in Kabupaten Karawang. Research with qualitative approach based on postpositivesme philosophy, is used to examine the natural object condition where the researcher is as the key instrument, the sampling of the data source is done purposively, the collecting technique with triangulation, the data analysis is inductive / qualitative, and the result of more qualitative research Emphasizing the meaning of generalization. From the results of research, obtained the following conclusions: (1). Non-Employee Cooperatives in Kabupaten Karawang that have been established Implementation Strategy management is still not optimal, (2). The concept of competitiveness of non-Employee Cooperatives in Kabupaten Karawang as an independent economic institution, has not been applied, (3). Constraints faced by cooperatives in facing the competitiveness of cooperatives implicate inhibiting the ability of the competitiveness of cooperatives in Karawang regency, especially Human Resources which is the main resources as a driver of cooperatives and strategic management of human centered cooperatives, (4). Cooperative development strategies in an effort to increase competitiveness require development and require the attention of various parties. Furthermore, the established cooperatives should apply strategic management by applying the organization's and management's standards seen from the organization. Keywords: Cooperative, Strategic Management, Competitiveness.